Uji Klinis Penggunaan Pasta Gigi Herbal Terhadap Penurunan Indeks Plak Rongga Mulut (Clinical Trial of Herbal Toothpaste to Reduce Plaque Index in Oral Cavity ) - Danang Dewantara Ananda Putra; Pudji Astuti; Abdul Rochim (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Toothpaste with a toothbrush are control hygiene and health of the oral cavity by means of cleaning plaque and food residues. Maintenance of teeth and cleaning the mouth is one of the efforts to improve health, but there are many people did not know is there a difference in cleaning the plaque herbals toothpastes. Objective: To compare plaque index pre and post given herbal toothpaste, and compare plaque index among herbal toothpaste. Methods: Research clinical trials that followed by 15 subject of study was more than 12 years old or arrangement of teeth complete permanent eruptive. Fifteen the subject divided into three groups using pre post test control group design and cross over design, the subject of brushing teeth with three different toothpaste. Result: Paired t-test result showed (p<0,05) there was significant reduction of plaque index between pre and post intervension herbal toothpaste and control toothpaste. One Way Annova test showed (p>0,05) there was no significant differences between those toothpaste to reduce plaque index. Conclusion: All of herbal toothpaste significant reduction of plaque index between pre and post intervension. There was no significant differences between those herbal toothpaste to reduce plaque index. Keywords: plaque index, herbal toothpaste